2007
DOI: 10.1007/s11661-006-9041-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Fluctuations and 1/f Noise in Dry Friction Dynamics

Abstract: This article presents experimental results that strongly suggest that the friction force vs time signal in dry friction experiments, carried out under strong wearing effects, shows self-similar fluctuations. Dry friction experiments were carried out in a pin-on-disk machine at loads in the range of 2 to 10 N and linear speeds from 0.05 to 25 cm/s, on SAE 52100 steel and AA5588 aluminum alloy samples. Alumina pins (actually spheres) were used throughout. The power spectra of the friction force vs time signal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The studies showed that such a phenomenon did not occur for the 100Cr6 balls. In the particular case of ceramic sliding over metals, fragments of metal adhere to the ceramic to form a transfer film [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies showed that such a phenomenon did not occur for the 100Cr6 balls. In the particular case of ceramic sliding over metals, fragments of metal adhere to the ceramic to form a transfer film [ 36 ].…”
Section: Resultsmentioning
confidence: 99%